Structure, hydration, and chloride ingress in C-S-H: Insight from DFT calculations. (March 2020) - Svenum, Ingeborg-Helene; Ringdalen, Inga G.; Bleken, Francesca L.; Friis, Jesper; Höche, Daniel; Swang, Ole
Abstract: The structure of Calcium-Silicate-Hydrate (C-S-H) and the effect of variations in its water content have been investigated using density functional theory (DFT) calculations. Trends for calculated densities as a function of hydration are in good agreement with experimental values, and in line with what is found using molecular mechanics in the literature. While we observe very little variation in SiO and CaO bond lengths between different structures, structural diversity is otherwise great, in accordance with experimental observations, as we see no obvious correlation between structural features and material system stability. A mapping of energetics of hydroxyl substitution with chloride reveals, unsurprisingly, that chloride preferentially coordinates to calcium. More specifically, it was found that the most stable sites for chlorine substitution involves at least two adjacent calcium atoms. Computed chloride substitution energies indicate that the C-S-H phase may bind chloride from aqueous solution, potentially influencing chloride diffusion in concrete.